Ceramic filter slurry and application thereof
By using a combination of composite powder and a variety of thickeners in the ceramic filter slurry, the problem of slurry viscosity is solved, and the stable slurry hanging and high pass rate of the ceramic filter are achieved.
Patent Information
- Application Number
- CN202411466908.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-21
AI Technical Summary
During the slurry slurry of existing ceramic filters, the viscosity of the existing ceramic filter slurry is not enough to affect the stability, and if the viscosity is too large, it is easy to form bumps, affecting the dimensional stability and surface flatness of the filter.
Use composite powder, alkali swelling thickener, associative thickener, sodium hydroxide aqueous solution, silicon sol, polyvinyl alcohol and solvent to adjust the viscosity and fluidity of the slurry to ensure the bulge point after slurry hanging Natural leveling.
The stable slurry hanging effect of the slurry is achieved, the dimensional stability and surface flatness of the ceramic filter are improved, and the filter pass rate is improved.
Smart Images

Figure CN119409520A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic product preparation technology, and in particular relates to a ceramic filter slurry and the application of the slurry in ceramic slurry hanging. Background Art
[0002] At present, the ceramic filters used for casting are relatively mature. In practical applications, ceramic filters have extremely strict requirements on appearance and size. In order to achieve better filtering effect, the dimensional error between filters and between filters and runners needs to be as small as possible. However, the production process of the filter is produced by sponge slurry hanging process. At present, the slurry used in the sponge slurry hanging process faces the problem that the slurry viscosity is too low to be conducive to slurry hanging in the process of preparing ceramic filters, and the slurry viscosity is too high and it is easy to produce bumps on the surface after slurry hanging, which affects the stability of the ceramic filter. Ceramic filters have strict requirements on appearance and size. The stability here refers to the dimensional stability of the filter. Including the filter pore size, the length, width and height of the filter and the surface flatness of the filter.
[0003] Therefore, in order to meet the needs of actual applications, it is urgent to develop a slurry that can stabilize the slurry hanging effect and improve the stability of the filter. Summary of the invention
[0004] In order to solve at least one of the above problems, the present invention provides a slurry for a ceramic filter, the components of which include composite powder, thickener, sodium hydroxide aqueous solution, silica sol, polyvinyl alcohol, and solvent.
[0005] in,
[0006] The thickener includes an alkali swelling thickener and an associative thickener;
[0007] The composite powder includes silicon carbide, silicon powder and aluminum oxide.
[0008] According to a specific embodiment of the present invention, in the slurry, the weight ratio of the composite powder, the alkali swelling thickener, the associative thickener, the sodium hydroxide aqueous solution, the silica sol, the polyvinyl alcohol and the solvent is (70-80): (0.2-0.8): (1-2): (0.3-0.5): (5-8): (3-5): (6-10).
[0009] According to a specific embodiment of the present invention, in the composite powder, the mass ratio of silicon powder, aluminum oxide and silicon carbide is (20-40): (20-45): (150-250). Within this range, the filter prepared by the present invention has the best stability.
[0010] According to a specific embodiment of the present invention, the associative thickener comprises an associative polyurethane leveling thickener.
[0011] According to a specific embodiment of the present invention, the solvent is water.
[0012] The second aspect of the present invention provides use of the slurry described in the first aspect in preparing a ceramic filter.
[0013] A third aspect of the present invention provides a method for preparing a ceramic filter, comprising:
[0014] A. dissolving and swelling sodium hydroxide aqueous solution, silica sol and polyvinyl alcohol in water to obtain a mixed solution 1;
[0015] B. adding an alkali-swellable thickener to the mixed solution 1 to swell the mixed solution to obtain a mixed solution 2;
[0016] C. adding the composite powder to the mixed solution 2 to obtain a mixed solution 3;
[0017] D. adding an associative thickener to the mixed solution 3 to obtain a ceramic filter slurry;
[0018] E. injecting the ceramic filter slurry into a sponge mold for slurry treatment to obtain the ceramic filter,
[0019] in,
[0020] The composite powder includes silicon carbide, silicon powder and aluminum oxide.
[0021] The present invention uses an associative leveling thickener and an alkali swelling thickener to modify the slurry. The alkali swelling thickener is used to increase the basic viscosity of the slurry to ensure the slurry hanging performance of the slurry. The associative leveling thickener is used to change the flow performance of the slurry in the slurry hanging, so that the convex points can be naturally leveled in a short time after the slurry is hung. The two thickeners work together to achieve the effect of stabilizing the hanging, thereby improving the final stability of the filter.
[0022] According to a specific embodiment of the present invention, in the ceramic filter slurry, the weight ratio of the composite powder, the alkali swelling thickener, the associative thickener, the sodium hydroxide aqueous solution, the silica sol, the polyvinyl alcohol and the solvent is (70-80): (0.2-0.8): (1-2): (0.3-0.5): (5-8): (3-5): (6-10).
[0023] According to a specific embodiment of the present invention, in the composite powder, the mass ratio of silicon powder, aluminum oxide and silicon carbide is (20-40): (20-45): (150-250).
[0024] According to a specific embodiment of the present invention, the pH of the ceramic filter slurry is 8.8-9.5.
[0025] The third aspect of the present invention provides a ceramic filter prepared by the method described in the second aspect.
[0026] The present invention uses an associative leveling thickener and an alkali swelling thickener to modify the slurry. The alkali swelling thickener is used to increase the basic viscosity of the slurry to ensure the slurry hanging performance of the slurry. The associative leveling thickener is used to change the flow performance of the slurry in the slurry hanging, so that the convex points can be naturally leveled in a short time after the slurry is hung. The two thickeners work together to achieve the effect of stabilizing the hanging, thereby improving the final stability of the filter. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1 The surface morphology of the ceramic filter prepared according to the method of Example 1 of the present invention;
[0029] Figure 2 It is an intermediate form of the slurry prepared by the method of Comparative Example 1 of the present invention;
[0030] Figure 3 The surface morphology of the ceramic filter prepared according to the method of Comparative Example 2 of the present invention;
[0031] Figure 4 The surface morphology of the ceramic filter prepared according to the method of Comparative Example 3 of the present invention;
[0032] Figure 5 The surface morphology of the ceramic filter prepared according to the method of Comparative Example 4 of the present invention;
[0033] Figure 6 This is the surface morphology of the ceramic filter prepared according to the method of Comparative Example 5 of the present invention. DETAILED DESCRIPTION
[0034] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0035] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.
[0036] In this document, the terms “contain”, “include” or “comprise” are open expressions, that is, they include the contents specified in the present invention but do not exclude other contents.
[0037] As used herein, the terms "optionally", "optional" or "optionally" generally mean that the subsequently described event or circumstance may but need not occur, and that the description includes instances where the event or circumstance occurs and instances where it does not.
[0038] In this article, the term "polyvinyl alcohol" is an organic compound with the chemical formula [C2H4O]n. It is a white flake, flocculent or powdery solid and odorless. It is soluble in water (above 95°C), slightly soluble in dimethyl sulfoxide, and insoluble in gasoline, kerosene, vegetable oil, benzene, toluene, ethylene dichloride, carbon tetrachloride, acetone, ethyl acetate, methanol, ethylene glycol, etc. Polyvinyl alcohol is an important chemical raw material used to make polyvinyl acetal, gasoline-resistant pipes and vinylon, fabric treatment agents, emulsifiers, paper coatings, adhesives, glues, etc.
[0039] In this article, the term "silicon powder" refers to a non-toxic, odorless, and pollution-free inorganic non-metallic material. Due to its excellent properties such as good temperature resistance, acid and alkali corrosion resistance, high thermal conductivity, high insulation, low expansion, stable chemical properties, and high hardness, it is widely used in chemical, electronic, integrated circuit (IC), electrical appliances, plastics, coatings, advanced paints, rubber, national defense and other fields. With the rapid development of high technology, silicon powder will also enter a new historical development period. Silica powder is a micropowder made from natural quartz (SiO2) or fused quartz (amorphous SiO2 after natural quartz is melted at high temperature and cooled) through multiple processes such as crushing, ball milling (or vibration, air flow milling), flotation, pickling purification, and high-purity water treatment.
[0040] In the present invention, silicon carbide includes silicon carbide C-DUST and silicon carbide (325) mesh. By weight, the silicon carbide C-DUST is 40-60 parts, and the silicon carbide (325) mesh is 100-200 parts.
[0041] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention provides drawings, which are part of the disclosure of the present invention. They are mainly used to illustrate the embodiments and can be used in conjunction with the relevant descriptions in the specification to explain the operating principles of the embodiments. By referring to these contents, ordinary technicians in this field should be able to understand other possible implementation methods and advantages of the present invention.
[0042] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] Example 1
[0044] 1. At room temperature, add 830g of water, 30g of sodium hydroxide aqueous solution (32% sodium hydroxide solution), 600g of silica sol (purchased from Shandong Better New Materials Co., Ltd.), and 400g of polyvinyl alcohol (purchased from Anhui Wanwei High-tech Materials Co., Ltd.) into a high-speed dispersing and stirring device to dissolve and swell, and stir evenly;
[0045] 2. Add 40g of alkali swelling thickener TT-935 (purchased from Dow Chemical), stir for 30 minutes to fully swell and dissolve, and stir evenly;
[0046] 3. Add 80g of mixed powder and stir evenly. The mixed powder is calculated by mass: 30 parts of silicon micropowder (purchased from Tianjin Yune International Trade Co., Ltd.), 40 parts of alumina (purchased from Shandong Aotai Electric Co., Ltd.), 50 parts of silicon carbide C-DUST (purchased from Tianjin Yune International Trade Co., Ltd.), and 150 parts of silicon carbide (325) mesh (purchased from Tianjin Yune International Trade Co., Ltd.);
[0047] 4. Add 100g associative polyurethane leveling thickener N-150 (purchased from Hefei Huayue New Material Technology Co., Ltd.) , Stir well;
[0048] 5. Carry out slurrying. The mixed slurry is pressed onto a polyurethane sponge (purchased from Weihai Jingsheng) through an immersion sizing process. After multiple roller pressing slurrying, the slurry is evenly distributed on the sponge. After drying, a ceramic filter is obtained.
[0049] The inventors found that the ceramic filter (such as Figure 1 The viscosity between the slurries and between the slurry and the sponge used for slurry hanging is shown in the figure. The surface of the ceramic filter is flat, without obvious protrusions and is not easy to collapse. The powder is evenly distributed without obvious pore blocking.
[0050] Comparative Example 1
[0051] Compared with Example 1, the difference of this example is that a cellulose thickener is used in step 2.
[0052] The inventors found that the use of cellulose thickeners would result in excessively high initial viscosity, and during the powder dispersion process, the temperature would be too high, causing the slurry to form a crust before use (e.g. Figure 2 As shown), subsequent slurry treatment is not possible.
[0053] Comparative Example 2
[0054] Compared with Example 1, the difference of this example is that step 4 is removed and the associative polyurethane leveling thickener N-150 is not added to the entire slurry.
[0055] The inventors found that the ceramic filter (such as Figure 3 As shown in the figure, the viscosity between the slurries and between the slurry and the sponge for slurry hanging is not enough, the slurry surface shows a tendency to collapse, and the collapsed surface is easy to break and fall into debris.
[0056] Comparative Example 3
[0057] Compared with Example 1, the difference of this example is that step 2 is removed and the alkali swelling thickener TT-935 is not added to the entire slurry.
[0058] The inventors have found that ceramic filters (such as Figure 4 As shown in the figure, the initial viscosity of the slurry is too low and the powder is unevenly dispersed.
[0059] Comparative Example 4
[0060] Compared with Example 1, the difference of this example is that one portion of alkali swelling thickener TT-935 is added in step 2.
[0061] The inventors found that when the alkali swelling thickener is added in excess, the prepared ceramic filter (such as Figure 5 As shown in the figure, the viscosity of the slurry is too high, which can easily block the pores on the surface of the sponge when the sponge is coated with slurry, thereby affecting the passing rate of the molten iron in the pouring.
[0062] Comparative Example 5
[0063] Compared with Example 1, the difference of this example is that 4 parts of associative polyurethane leveling thickener N-150 are added in step 4.
[0064] The inventors found that when the added associative polyurethane leveling thickener N-150 was excessive, the prepared ceramic filter (such as Figure 6As shown), the slurry viscosity is too high, there are many protrusions on the surface, the protrusions are easily broken, and the prepared ceramic filter is unstable.
[0065] Comparative Example 6
[0066] Compared with Example 1, the difference of this example is that no thickener is added to the slurry.
[0067] The inventors found that the ceramic filter prepared without adding any thickener did not have major defects on the surface, but the average compressive strength after molding was only 1.18 MPa, while the average compressive strength in Example 1 was increased to 2.87 MPa, which did not meet the filter strength requirements.
[0068] Take 100 ceramic filters prepared with the slurry in the above-mentioned embodiments and comparative examples, and measure the qualified rate of the ceramic filters. When convex spots, blocked holes, and collapse appear on the surface of the ceramic filters, and the compressive strength of the prepared ceramic filters is not higher than 1.2 MPa, they are judged to be unqualified. The measurement results are shown in Table 1.
[0069] Table 1
[0070]
[0071]
[0072] The inventor used the slurry described in Example 1 to coat the sponge with slurry, and found that the qualified rate of coating was significantly improved. In Comparative Example 1, the inventor initially tried to use cellulose thickeners such as hydroxymethyl cellulose and hydroxyethyl cellulose. In the actual process, it was found that the use of cellulose thickeners would make the viscosity of the system too high, and the powder in the slurry would easily form agglomerates, and the dispersion effect was extremely poor. Subsequently, the thickener in step 2 was used as this alkali swelling type thickener, and the aggregate in the slurry could be stably dispersed. It was also tried to add two thickeners A / B in this step. Since the system has a lot of powder, the powder was not wetted during the early powder dispersion process, resulting in excessive internal friction and too high slurry temperature. It needs to be cooled. Otherwise, subsequent normal production cannot be carried out.
[0073] In comparative example 2, the inventors tried not to add the associative thickener in the last step for relevant comparison. The inventors found that if only the front-end thickener was used, the slurry could be hung relatively stably, but the filter failure rate caused by the convex points was about 10-12%. After the associative thickener was added in the last step, the filter failure rate caused by the convex points was about 6-8%.
[0074] Alkali swelling thickeners can quickly increase the viscosity of the system under alkaline conditions, combine with powders under high shear conditions, and evenly disperse the powders in the mixed emulsion. Maintain good dispersion of the powder; the biggest feature of the associative thickener is that it can ensure excellent viscosity stability under high shear conditions, and has good fluidity under low shear conditions. The combination of the two thickeners ensures the stability of the slurry viscosity under shear conditions during the sponge slurry hanging process. After the slurry is hung, during the static process, due to the disappearance of shear force, the associative thickener ensures the natural leveling of the bumps.
[0075] In summary, the inventors of the present application improved the stability of the produced ceramic filters by adding a thickener to the slurry for preparing the ceramic filters. Furthermore, the inventors screened a variety of thickeners and screened out the slurry components and the best component ratio that are most suitable for the sponge slurry hanging process. Compared with the slurry in the prior art, the ceramic filters prepared using the slurry provided by the present invention increased the pass rate of the ceramic filters by 2-10%.
[0076] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A slurry for a ceramic filter, characterized in that: The slurry comprises composite powder, thickener, sodium hydroxide aqueous solution, silica sol, polyvinyl alcohol, and solvent. in, The thickener includes an alkali swelling thickener and an associative thickener; The composite powder includes silicon carbide, silicon powder and aluminum oxide.
2. The slurry according to claim 1, characterized in that In the slurry, the weight ratio of the composite powder, the alkali swelling thickener, the associative thickener, the sodium hydroxide aqueous solution, the silica sol, the polyvinyl alcohol and the solvent is (70-80): (0.2-0.8): (1-2): (0.3-0.5): (5-8): (3-5): (6-10).
3. The slurry according to claim 1, characterized in that In the composite powder, the mass ratio of silicon powder, aluminum oxide and silicon carbide is (20-40): (20-45): (150-250).
4. The slurry according to claim 1, characterized in that The associative thickener includes an associative polyurethane leveling thickener; The solvent is water.
5. Use of the slurry according to any one of claims 1 to 4 in the preparation of a ceramic filter.
6. A method for preparing a ceramic filter, characterized in that: include: A. dissolving and swelling sodium hydroxide aqueous solution, silica sol and polyvinyl alcohol in water to obtain a mixed solution 1; B. adding an alkali-swellable thickener to the mixed solution 1 to swell the mixed solution to obtain a mixed solution 2; C. adding the composite powder to the mixed solution 2 to obtain a mixed solution 3; D. adding an associative thickener to the mixed solution 3 to obtain a ceramic filter slurry; E. injecting the ceramic filter slurry into a sponge mold for slurry treatment to obtain the ceramic filter, in, The composite powder includes silicon carbide, silicon powder and aluminum oxide.
7. The method according to claim 6, characterized in that In the ceramic filter slurry, the weight ratio of the composite powder, the alkali swelling thickener, the associative thickener, the sodium hydroxide aqueous solution, the silica sol, the polyvinyl alcohol and the solvent is (70-80): (0.2-0.8): (1-2): (0.3-0.5): (5-8): (3-5): (6-10).
8. The method according to claim 6, characterized in that In the composite powder, the mass ratio of silicon powder, aluminum oxide and silicon carbide is (20-40): (20-45): (150-250).
9. The method according to claim 6, characterized in that The pH of the ceramic filter slurry is 8.8-9.
5.
10. A ceramic filter, characterized in that: Prepared by the method described in any one of claims 6 to 9.
Citation Information
Patent Citations
Silicon carbide foam ceramic filter
CN101164655A
Waterborne primer for fiber reinforced epoxy resin composite material and preparation method thereof
CN109251647A
Water-based strippable coating, preparation method and application
CN114213927A
Thickener blend composition and method for thickening aqueous systems
US20080234425A1
Composition and method for roads, parking lots, and driving surfaces
US20140356526A1